2018
DOI: 10.3390/su10103650
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Value on Farmers’ Regret Mood Tendency

Abstract: Based on a survey of the poverty alleviation resettlement (PAR) farmers in China, this paper aims to investigate the relationship between the expected value, perceived value and regret mood of the relocated farmers. The results show that the expected value can positively affect the perceived value, and the latter negatively impact the regret mood of the PAR farmers. On average, the farmers with regret and non-regret sentiments are approximately fifty/fifty in percentage terms. Internal factors, such as demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, when farmers make accurate decisions, perceived risks significantly impact farmers' green agricultural production behaviors [26]. In addition, relevant studies have found that individual behavioral decisions result from perceived values formed after weighing and comparing perceived benefits and risks [57]. Therefore, in the decision-making process for farmland quality protection, if the expected protection benefits of farmers are more significant than the expected cost, then the farmers' perceived value of farmland quality protection will be high, and the condition becomes conducive to the implementation of farmland quality protection behavior by farmers.…”
Section: Hypotheses 5 (H5)mentioning
confidence: 99%
“…However, when farmers make accurate decisions, perceived risks significantly impact farmers' green agricultural production behaviors [26]. In addition, relevant studies have found that individual behavioral decisions result from perceived values formed after weighing and comparing perceived benefits and risks [57]. Therefore, in the decision-making process for farmland quality protection, if the expected protection benefits of farmers are more significant than the expected cost, then the farmers' perceived value of farmland quality protection will be high, and the condition becomes conducive to the implementation of farmland quality protection behavior by farmers.…”
Section: Hypotheses 5 (H5)mentioning
confidence: 99%
“…It is the phenomenon of asymmetry which may significantly shape the perceived value of farmers' behavior, while government embeddedness usually targets the removal of the barriers by empowering farmers with recognition and enhancing social acceptance [123]. Second, farmers' green production may need comprehensive self-interest, altruistic value, and social value [124]. When farmers perceive that green production can bring sufficient benefits to themselves, others, and society, they will take the lead in implementing green production [90].…”
Section: Hypothesis 7 (H7)mentioning
confidence: 99%
“…When farmers expected more gains in the PPWs green disposal behaviors, namely the PPWs green disposal behaviors can obtain better utility, perceived value level will be higher, and they are more inclined to adopt the green disposal behaviors; On the contrary, when farmers expected the gains to be less than the losses in the PPWs green disposal behaviors, namely when the results of PPWs green disposal cannot achieve utility and cause losses, the farmers' perceived value level will be lower, and they are more inclined to give up the green disposal behaviors. Other studies about farmers' emotions showed that perceived value had a significant impact on their regret mood tendency [53]. Research results in the field of green product marketing indicated that perceived value could positively affect individuals' purchase behaviors [33,54].…”
Section: Influence Of Perceived Value On Farmers' Green Disposal Behaviorsmentioning
confidence: 99%